2020
DOI: 10.1111/all.14667
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of CpG methylation improves the barrier integrity of bronchial epithelial cells in asthma

Abstract: 6. Atherton HC, Jones G, Danahay H. IL-13-induced changes in the goblet cell density of human bronchial epithelial cell cultures: MAP kinase and phosphatidylinositol 3-kinase regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…The inversion of CpG methylation diminishes epithelium leakiness and increases the expression of tight junctions' proteins. 61 Moreover, the methylation status of inflammatory genes differentiates asthma patients from non-asthmatic subjects. 62 Decreased methylation and low expression of vanin-1 gene are associated with poor response to inhaled corticosteroids (ICS), whereas increased availability of cysteamine, a product of vanin-1 pathway, protects from AHR.…”
Section: Shared Mechanismsmentioning
confidence: 99%
“…The inversion of CpG methylation diminishes epithelium leakiness and increases the expression of tight junctions' proteins. 61 Moreover, the methylation status of inflammatory genes differentiates asthma patients from non-asthmatic subjects. 62 Decreased methylation and low expression of vanin-1 gene are associated with poor response to inhaled corticosteroids (ICS), whereas increased availability of cysteamine, a product of vanin-1 pathway, protects from AHR.…”
Section: Shared Mechanismsmentioning
confidence: 99%
“…Another pioneer study of DNA methylation in nasal cells from asthmatics ( n = 35, Caucasian children population) showed that FeNO (fractional exhaled nitric oxide) is negatively associated with IL6 and iNOs methylation. While global methylation has been found higher in BECs of asthmatics, 30 Alu and LINE1‐global methylation was not linked to FeNO and FEV1 (Forced Expiratory Volume) in nasal epithelial cells (NECs). Decreased methylation of IL6 promoter was associated with higher FENO as shown in multivariable regression in an independent fashion of the iNOS promoter status.…”
Section: Dna Methylation In Nasal Epithelial Cells (Necs)mentioning
confidence: 97%
“…Another study did not directly measure methylation changes, but targeted epigenetic modifying enzymes instead and assessed expression of 82 genes across 5 families(30), with linear regression showing reduced mRNA expression of the kinase Aurora Kinase A (AURKA), the ligase DZIP3, the methyltransferases Euchromatic Histone Lysine Methyltransferase 2 (EHMT2) and Suppressor Of Variegation three to nine Homolog 1 (SUV39H1), as well as increased mRNA expression of the acetyltransferases CREB Binding Protein (CREBBP) and E1A Binding Protein P300 (EP300). Notably, regarding genes involved in epigenetic processes, Tet Methylcytosine Dioxygenase 1 (TET1), which is involved in DNA demethylation, was found to be methylated in another study which used in air‐liquid interface cultures of asthmatic BECs, 30 whereas Protein Arginine Methyltransferase 1 (PRMT1), a histone methyltransferase, was not. The same study also found higher global methylation levels in asthmatic BECs, and their list of the top 100 group of highly methylated genes includes the previously mentioned LCN6, CCL26, CREBBP and TNXB, with several of the rest of the genes associated with cytoskeletal remodeling, cell growth, ion transport, metabolism, T‐cell signaling pathway, and bronchial barrier regulation (Table 1 ).…”
Section: Differential Dna Methylation In Bronchial Epithelial Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 138 ] Inhibition of CpG methylation was found to improve the integrity of the bronchial epithelial barrier in asthma. [ 139 ] Parkinson's disease-associated gene could also protect against HDM-induced airway epithelial barrier impairment by attenuating epithelial cell pyroptosis. [ 127 ] Nitric oxide promoted airway epithelial wound repair through increasing the activity of matrix metalloproteinases 9.…”
Section: Restoration Of the Airway Epithelial Barriermentioning
confidence: 99%